2017
DOI: 10.1038/cddis.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Kaiso depletion attenuates the growth and survival of triple negative breast cancer cells

Abstract: Triple negative breast cancers (TNBC) are highly aggressive and lack specific targeted therapies. Recent studies have reported high expression of the transcription factor Kaiso in triple negative tumors, and this correlates with their increased aggressiveness. However, little is known about the clinical relevance of Kaiso in the growth and survival of TNBCs. Herein, we report that Kaiso depletion attenuates TNBC cell proliferation, and delays tumor onset in mice xenografted with the aggressive MDA-231 breast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 63 publications
3
40
0
Order By: Relevance
“…It is noteworthy that in breast tumor cells expressing wild-type p53, Kaiso functions in a pro-apoptotic capacity [23]. This supports independent studies showing that Kaiso activates the pro-apoptotic gene APAF1 by forming a protein complex with wild-type p53, which in turn binds and activates the APAF1 promoter [24].…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Insupporting
confidence: 55%
See 4 more Smart Citations
“…It is noteworthy that in breast tumor cells expressing wild-type p53, Kaiso functions in a pro-apoptotic capacity [23]. This supports independent studies showing that Kaiso activates the pro-apoptotic gene APAF1 by forming a protein complex with wild-type p53, which in turn binds and activates the APAF1 promoter [24].…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Insupporting
confidence: 55%
“…We have observed a similar phenomenon with Kaiso; its interaction with wild-type p53 activates transcription of pro-apoptotic genes, while its interaction with mutant p53 potentially represses transcription of pro-apoptotic genes (Figure 1) [23, 24]. Additionally, a recent study showed that while Kaiso’s transcriptional activities were mostly repressive in HeLa cells, many pathways were also activated in the presence of Kaiso [25].…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations